Postoperative neurocognitive disorders - Tasbihgou, Setayesh Reza; Absalom, Anthony Ray (Korean journal of anesthesiology, 2021)
A decline in cognitive function is a frequent complication of major surgery. Postoperative cognitive impairments have generally been divided into short- (postoperative delirium) and long-term disturbances (postoperative cognitive dysfunction [POCD]). Long-term impairments are often subtle and overlooked. They need to be objectively assessed using neuropsychological tests to be diagnosed. Although POCD has been the subject of considerable research over the past decades, it remains uncertain why some patients do not return to preoperative levels of cognitive function. Surgery and anesthesia have both been implicated to play a role in POCD development, and certain patient-related factors, such as advanced age and low preoperative baseline cognitive function, have consistently been found to predict postoperative cognitive decline. This article will present an overview of POCD and its etiology and provide advice on possible strategies on its prevention.